Implementation of the Fahim Quran Method in Improving Students' Tahfidzh Quality at Nurul Ilmi Bekasi Integrated Islamic Elementary School - Alfanny, Iqbal Ramadhan; Muthi’, Ibnu; Baharuddin (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
In memorizing the Al-Qur'an is not an easy matter. Not everyone can memorize the Al-Qur'an. Given the different abilities of students. This study aims to determine the planning of the Tahfidzh Al Qur'an program and to determine the planning for implementing the Fahim Qur'an method in the Tahfidzh Al Qur'an subject at the Integrated Islamic Elementary School Nurul Ilmi Bekasi. This study uses a descriptive analysis research method with a qualitative approach. In collecting data in the field researchers used data collection methods through three techniques, namely: interviews, observation and documentation. Subjects in the research are school principals, teachers, students, or it could be portfolios which include: Reviews, reports, video recordings of student activities, photos/pictures, interview notes and others. The results of the study explain a clear and in-depth knowledge of Islamic Religious Education and the application of the Fahim Qur'an method in improving the quality of Tahfidzh of Integrated Islamic Elementary School students Nurul Ilmi Bekasi.